ANALISIS PENGARUH PERSEPSI KUALITAS PELAYANAN DAN PERCEIVED VALUE TERHADAP KEPUASAN RELIGIUS UNTUK MENINGKATKAN MINAT MENABUNG ULANG (Studi Pada BNI Syariah Semarang) - Hibba Al Kanzu; Harry Soesanto (Faculty of Economics and Business Diponegoro University, 2016)
The problem in this research is a decrease in the amount of third party funds (savings)are decreased and the high number of closing the savings account of Islamic banking.This research aims to test the power of perceived service quality and perceived value toreligious satisfaction to improve consumer resaving interest in an Islamic Banking insemarang (study in BNI Syariah). This study using three independent variable isperceived service quality and perceived value , variable resaving intention consumer as adependent variable and variable religious satisfaction as intervening.A method of this research technique using probability sample that is random samplingand clusters of sampling to sample as many as 100 of respondents in the middle class andover who had bought an apartment in semarang .A method of data analyst using atechnique double regression analysis , the analysis includes: test the validity of , a test ofreliability , test the assumption of the classics , linear regression test doublet test , test f ,test the coefficients determined and test sobel.The results show significant and positive effect perceived service quality to religioussatisfaction and resaving intention, significant and positive effect perceived value toreligious satisfaction and repurchase intention, and then significant and positive effectreligious satisfaction to repurchase intention.Keywords : Perceived Service Quality, Perceived Value, Religious Satisfaction,Repurchase Intention.